2009
DOI: 10.1152/japplphysiol.90735.2008
|View full text |Cite
|
Sign up to set email alerts
|

The role of time and pressure on alveolar recruitment

Abstract: Inappropriate mechanical ventilation in patients with acute respiratory distress syndrome can lead to ventilator-induced lung injury (VILI) and increase the morbidity and mortality. Reopening collapsed lung units may significantly reduce VILI, but the mechanisms governing lung recruitment are unclear. We thus investigated the dynamics of lung recruitment at the alveolar level. Rats (n = 6) were anesthetized and mechanically ventilated. The lungs were then lavaged with saline to simulate acute respiratory distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
127
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(150 citation statements)
references
References 41 publications
11
127
0
3
Order By: Relevance
“…A 40 cm H 2 O recruitment maneuver was applied for 30 s. They found that 50% of the recruited volume was attained within 1.6 s, 95% within 6.8 s, and Ͼ 98% with 10 s of applying the pressure. Further, blood pressure began dropping by 10 s and had decreased significantly at 20 s and 30 s. These observations of recruitment time are in agreement with a recent animal study showing that a majority of recruitment occurs within 2 s. 79 The editorial accompanying the Arnal article makes the case that the sustained pressure recruitment maneuver should be retired in favor of a stepwise increase using pressure ventilation, as it is better tolerated hemodynamically and the patient receives ventilation during the procedure. 80 Although recruitment maneuvers have been shown to improve short-term oxygenation, they have not been associated with improvement in any important outcomes, such as mortality, and should only be considered as part of rescue therapy for severe hypoxemia.…”
Section: Acute Lung Injury and Acute Respiratory Distress Syndromesupporting
confidence: 84%
“…A 40 cm H 2 O recruitment maneuver was applied for 30 s. They found that 50% of the recruited volume was attained within 1.6 s, 95% within 6.8 s, and Ͼ 98% with 10 s of applying the pressure. Further, blood pressure began dropping by 10 s and had decreased significantly at 20 s and 30 s. These observations of recruitment time are in agreement with a recent animal study showing that a majority of recruitment occurs within 2 s. 79 The editorial accompanying the Arnal article makes the case that the sustained pressure recruitment maneuver should be retired in favor of a stepwise increase using pressure ventilation, as it is better tolerated hemodynamically and the patient receives ventilation during the procedure. 80 Although recruitment maneuvers have been shown to improve short-term oxygenation, they have not been associated with improvement in any important outcomes, such as mortality, and should only be considered as part of rescue therapy for severe hypoxemia.…”
Section: Acute Lung Injury and Acute Respiratory Distress Syndromesupporting
confidence: 84%
“…12 for consecutive lung lobes from the complex analogue -see trends for Valv1 − Valv4. For the clinicians involved in the management of lung recruitment/de-recruitment during the mechanical ventilation it is interesting to know the moment of airway zone reopening/closure expressed as a function of pressure, volume or even time [15]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical and physical-mathematical models of alveolar zone, which have been proposed in the literature [15], apply to respiratory mechanisms proper for breathing at volumes lower than the total lung capacity (TLC) [16−19]. The recruitment manoeuvre, especially in patients with ARDS or ALI (acute lung injury), is performed near and even above the TLC level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recruitment is also a function of PEEP and time [8]. Therefore, true minimal E drs can only be determined after a stabilisation period is provided at each PEEP level.…”
Section: Discussionmentioning
confidence: 99%